OPTIMALISASI VIDEO EDUKASI: UPAYA MENINGKATKAN KESADARAN MASYARAKAT DALAM MEMATUHI PROTOKOL KESEHATAN DI ERA NEW NORMAL - Komarudin Komarudin; Laila Puspita (Universitas Serang Raya, 2022)
Early in 2020, we are welcomed by the Corona Virus Disease 2019 (Covid-19) outbreak. The lack of public awareness to always comply with health protocols is one of the triggers of the increasing number of Covid-19 spread in Indonesia. The lack of parental awareness of the importance of disciplining their children to always comply with health protocol regulations, such as not wearing a mask, not keeping distance, and awareness to wash their hands is one of the causes of the spread of covid-19. Therefore, efforts are needed to raise awareness of parents and children to comply with health protocols in the midst of the covid-19 outbreak through educational videos. This service is carried out by conducting socialization accompanied by the creation of children's educational videos about covid-19 and how health protocols should be carried out. This service was done to the villagers of Bagelen as many as 40 parents and their children. The instrument used in this study is a questionnaire of awareness of the master / child to the dangers of covid-19.